2015
DOI: 10.3389/fmed.2015.00031
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Interest to Use Deuteron Beams to Produce Non-Conventional Radionuclides?

Abstract: With the recent interest on the theranostic approach, there has been a renewed interest for alternative radionuclides in nuclear medicine. They can be produced using common production routes, i.e., using protons accelerated by biomedical cyclotrons or neutrons produced in research reactors. However, in some cases, it can be more valuable to use deuterons as projectiles. In the case of Cu-64, smaller quantities of the expensive target material, Ni-64, are used with deuterons as compared with protons for the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Another interesting study showed the uptake of 52g Mn-Mn 21 in monkeys after nostril administration of the radiotracer (37). Brain uptake in rhesus macaque monkeys was determined over 8 sessions with at least 6 mo between each session.…”
Section: Radiochemistry and Imaging Of 52 Mnmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting study showed the uptake of 52g Mn-Mn 21 in monkeys after nostril administration of the radiotracer (37). Brain uptake in rhesus macaque monkeys was determined over 8 sessions with at least 6 mo between each session.…”
Section: Radiochemistry and Imaging Of 52 Mnmentioning
confidence: 99%
“…52g Mn-Mn(oxinate) 2 was synthesized and determined to have suitable in vitro stability to study extravasation in vivo when conjugated with a liposomal nanomedicine (40). In another study, which leveraged the biologic properties of Mn 21 , 52g Mn 21 -Mn 21 was successfully used to image functional b-cell mass in mice with type 1 and type 2 diabetes (41). Finally, 52g Mn 21 -Mn 21 was used to investigate the biodistribution of manganese when administered intravenously or through inhalation (38).…”
Section: Radiochemistry and Imaging Of 52 Mnmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in three scandium radioisotopes, 43 Sc, 44g/m Sc and 47 Sc, in nuclear medicine has already been acknowledged and discussed in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] (the selected properties of these radioisotopes are summarized in Table 1). Both positron emitters 43 Sc and 44g Sc are promising PET radioisotopes that can compete with the commonly used 68 Ga [1][2][3][4][5], while 44g Sc offers unique possibilities in the three-photon PET technique [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Both positron emitters 43 Sc and 44g Sc are promising PET radioisotopes that can compete with the commonly used 68 Ga [1][2][3][4][5], while 44g Sc offers unique possibilities in the three-photon PET technique [6][7][8]. Additionally, 44m Sc can be used as a 44m Sc/ 44g Sc long-lived in-vivo generator as it decays mainly by a low energy transition to the ground state [9][10][11][12]. Meanwhile, 47 Sc is a β-emitter suitable for both therapeutic purposes and SPECT imaging [13], which is emphasized also within the IAEA Coordinated Research Project [14,15].…”
Section: Introductionmentioning
confidence: 99%